Dotted Core–Shell Nanoparticles for T1‐Weighted MRI of Tumors. Issue 33 (4th July 2018) - Shen, Zheyu; Song, Jibin; Zhou, Zijian; Yung, Bryant C.; Aronova, Maria A.; Li, Yan; Dai, Yunlu; Fan, Wenpei; Liu, Yijing; Li, Zihou; Ruan, Huimin; Leapman, Richard D.; et al.
Abstract: Gd‐based T 1 ‐weighted contrast agents have dominated the magnetic resonance imaging (MRI) contrast agent market for decades. Nevertheless, they are reported to be nephrotoxic and the U.S. Food and Drug Administration has issued a general warning concerning their use. In order to reduce the risk of nephrotoxicity, the MRI performance of the Gd‐based T 1 ‐weighted contrast agents needs to be improved to allow a much lower dosage. In this study, novel dotted core–shell nanoparticles (FeGd‐HN3‐RGD2) with superhigh r 1 value (70.0 mM −1 s −1 ) and very low r 2 / r 1 ratio (1.98) are developed for high‐contrast T 1 ‐weighted MRI of tumors. 3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assay and histological analyses show good biocompatibility of FeGd‐HN3‐RGD2. Laser scanning confocal microscopy images and flow cytometry demonstrate active targeting to integrin αv β3 positive tumors. MRI of tumors shows high tumor ΔSNR for FeGd‐HN3‐RGD2 (477 ± 44%), which is about 6‐7‐fold higher than that of Magnevist (75 ± 11%). MRI and inductively coupled plasma results further confirm that the accumulation of FeGd‐HN3‐RGD2 in tumors is higher than liver and spleen due to the RGD2 targeting and small hydrodynamic particle size (8.5 nm), and FeGd‐HN3‐RGD2 is readily cleared from the body by renal excretion. Abstract : FeGd‐HN3‐RGD2 dotted core–shell nanoparticles have a superhigh r 1 value (70.0 mM −1 s −1 ) and very low r 2 / r 1 ratio (1.98), and are actively targetable to the integrin αv β3 positive tumors. Magnetic resonance imaging of tumors shows a superhigh tumor ΔSNR (477 ± 44%), which is much higher than that of the popular commercial Magnevist (75 ± 11%).